Do we need to keep Increasing Crop Productivity for all Times to Come? - Narain, Prem (Journal of Agronomy Research, 2020)
This commentary questions the presumption of ever‑increasing crop productivity as the singular goal. It weighs diminishing returns and ecological costs against diversification, efficiency, and demand‑side measures. The authors argue for context‑specific targets that prioritize nutrition, resilience, and sustainability over yield expansion alone.
Keywords: Vertical dimension; Crop productivity; Per Capita availability of food.